Kidstuff a computer aided instruction for educable mentally retarded children in the primary level - Calderon, Maricel B. (1997)
In the Philippines, most computer applications in education are designed for students without developmental disabilities. Few cater to the needs of special children. This study intends to come up with a computer application that will address the instructional needs of mentally handicapped learners, particularly educable mentally retarded (EMR) children in the primary level with developmental age ranging from 5 to 6 years. It should be emphasized that it will only supplement, rather than replace, teacher-delivered instruction. Our goal is to help the children acquire fundamental skills in reading, language arts, and mathematics. This computer-aided instruction software will be based on techniques and instruction materials suited to the children's needs, interests and learning capacities. Instruction will be in either Filipino or English, and the lessons presented will reflect Philippine culture and society. Intensive research has been done on the characteristics and the behavior of EMR children in the primary, in order to meet their needs. Other research areas included are the teaching principles and strategies which are essential in coming up with an effective instructional design. Based on these, lesson plans had been prepared. Further study has also been conducted on the use of computers as powerful interactive learning tools that present individualized programs to all children. Another research area is multimedia since the software has full audio, and graphics support, being a Windows based application.